2013
DOI: 10.1021/jp405068q
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of an Intermediate Temperature Molten Lithium Salt Based on Fluorosulfonyl(trifluoromethylsulfonyl)amide as a Solvent-Free Lithium Battery Electrolyte

Abstract: The asymmetric amide anion, such as (fluorosulfonyl)(trifluoromethylsulfonyl)amide (fTfN–), formed intermediate temperature molten lithium salts at 100 °C, which was the lowest among the lithium single molten salts composed of conventional halogenide, nitrate, perchlorate, and perfluoro anions. The molten Li[fTfN] was highly viscous (17 Pa·s at 110 °C, however, it was classified as a good ionic liquid by Walden plot analysis, which indicates the good-dissociation between Li+ and fTfN–. Due to the high transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 48 publications
(83 reference statements)
2
50
0
Order By: Relevance
“…A situation similar to the PEC electrolyte may have occurred in these highly concentrated liquid electrolytes. Also, Kubota and Matsumoto reported a very high t + for molten lithium (fluorosulfonyl)(trifluoromethylsulfonyl)imide. We believe that the aggregated ions in the highly concentrated PEC electrolytes exist like a molten salt, in which C=O groups cause the aggregated ions to be molten and movable, without tightly coordinating to Li + .…”
Section: Resultsmentioning
confidence: 99%
“…A situation similar to the PEC electrolyte may have occurred in these highly concentrated liquid electrolytes. Also, Kubota and Matsumoto reported a very high t + for molten lithium (fluorosulfonyl)(trifluoromethylsulfonyl)imide. We believe that the aggregated ions in the highly concentrated PEC electrolytes exist like a molten salt, in which C=O groups cause the aggregated ions to be molten and movable, without tightly coordinating to Li + .…”
Section: Resultsmentioning
confidence: 99%
“…It was quite interesting that both the melting point and viscosity have the same tendency toward the size of the anion. The Li[fTfN] can be used as a onium-free lithium single molten salt from 100 °C to the decomposition temperature (300 °C) [ 57 ]. Such an onium-free lithium single salt will be useful to focus on the latent potential and also the limitation of perfl uoroanions for battery applications.…”
Section: New Ionic Liquids Composed Of New Anions Developed During Thmentioning
confidence: 99%
“…5 The synthesized products were identified by elemental analysis. Residual moisture was confirmed to be below 50 ppm by a Karl Fischer moisture meter (MITSUBISHI, CA-07).…”
Section: Methodsmentioning
confidence: 99%
“…We reported that lithium (fluorosulfonyl)(trifluoromethylsulfonyl)amide, denoted as Li[fTfN], can be used as a molten salt electrolyte for the lithium secondary battery without dissolving it in organic solvents, room temperature ionic liquids (RTIL), and even the other alkali metal salts. 5 Furthermore, its cation mixture can be used around room temperature and its lithium secondary battery showed higher rate performance and cycle stability. 6 In order to apply the novel low-melting molten salts, it is significant to investigate their physicochemical and electrochemical properties.…”
Section: Introductionmentioning
confidence: 99%